2020
DOI: 10.4136/ambi-agua.2495
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow regionalization for the Mortes River Basin upstream from the Funil Hydropower Plant, MG

Abstract: Maximum and minimum streamflow are fundamental for water resource management, especially for water rights. However, lack of monitoring and scarce streamflow data limit such studies. Streamflow regionalization is a useful tool to overcome these limitations. The study developed models for regionalization of the maximum and minimum reference streamflows for the Mortes River Basin (MRB) (Water Resources Planning and Management Unit - GD2), Southern Minas Gerais State. The study used long-term streamflow historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Regarding Q 7,10 (6.9 m 3 s −1 ), for the streamflow that is used as a basis for granting water resources in the region, the PDF that presented the best fitting was Wakeby, with AD equal to 0.30. Amorim et al [29] found a similar result in the Mortes River, Southeastern Brazil, demonstrating the satisfactory performance of this PDF for the Q 7 series. The SY 7,10 was equal to 2.1 L s −1 km −2 , similar to that obtained by Silva et al [6] in the Minas Gerais State.…”
Section: Hydrological Behaviormentioning
confidence: 65%
See 1 more Smart Citation
“…Regarding Q 7,10 (6.9 m 3 s −1 ), for the streamflow that is used as a basis for granting water resources in the region, the PDF that presented the best fitting was Wakeby, with AD equal to 0.30. Amorim et al [29] found a similar result in the Mortes River, Southeastern Brazil, demonstrating the satisfactory performance of this PDF for the Q 7 series. The SY 7,10 was equal to 2.1 L s −1 km −2 , similar to that obtained by Silva et al [6] in the Minas Gerais State.…”
Section: Hydrological Behaviormentioning
confidence: 65%
“…The Q mean was obtained from the average of the daily streamflow, while the Q min and Q max were obtained from the average of the minimum and maximum daily annual streamflow, respectively. To obtain Q 7,10 , 10 PDFs fitted using the L-moments were analyzed [29]: the 3-parameter log-normal (LN3), 3-parameter Pearson (PE3), the Gumbel extreme value, the Generalized Extreme Values (GEV), Gamma, Weibull, the 4-parameter Kappa, the 5-parameter Wakeby, the generalized logistic (GLO), and the generalized Pareto (GPA). The PDF was then selected based on the best fitting according to the Anderson-Darling (AD) test.…”
Section: Hydrological Indicatorsmentioning
confidence: 99%
“…Moreover, Rahman et al ( 2014) assessed WAK's applicability in Australia and reached the same conclusion; thus, they recommended the use of this PDF for the probabilistic modeling of flood events in that country. Similarly, Amorim et al (2020), in a study applied to the Mortes River basin, Brazil, concluded that WAK was one of the most appropriate PDFs for probabilistic modeling of floods events.…”
Section: Resultsmentioning
confidence: 98%